Prevalences of Parental and Peer Support and Their Independent Associations With Mental Distress and Unhealthy Behaviours in 53 Countries - Lian Li; Guodong Xu; Dongsheng Zhou; Ping Song; Yucheng Wang; Guolin Bian (Frontiers Media S.A., 2022)
Objective: Parental and peer support are both associated with mental distress and unhealthy behaviour indices in adolescents.Methods: We used the Global School-Based Student Health Survey data (n = 192,633) from 53 countries and calculated the weighted prevalence of individual and combined parental and peer support. Multiple logistic regression analysis was used to estimate the adjusted associations between combined parental and peer support with mental distress and unhealthy behaviours.Results: The prevalence figures for having all four categories of parental support and two peer-support were 9.7% and 38.4%, respectively. Compared with no parental support, adolescents with all four parental support negatively associated with all five mental distress and eight unhealthy behaviours factors, and the ORs ranged from 0.19 to 0.75. Additionally, adolescents with two peer support were negative association with all mental distress and four health risk behaviours, and positively associated with a sedentary lifestyle.Conclusion: Parental and peer support were lacking in some countries, while greater parental and peer support were negative associated with mental distress and most unhealthy behaviours in adolescents, and the relationships were independent.